Sulindac derivatives inhibit cell growth and induce apoptosis in primary cells from malignant peripheral nerve sheath tumors of NF1-patients - Frahm, Silke (BioMed Central, 2004)
BACKGROUND: Malignant peripheral nerve sheath tumors (MPNSTs) are neoplasms leading to death in most cases. Patients with Neurofibromatosis type 1 have an increased risk of developing this malignancy. The metabolites of the inactive prodrug Sulindac, Sulindac Sulfide and Sulindac Sulfone (Exisulind) are new chemopreventive agents that show promising results in the treatment of different cancer types. In this study we examined the antineoplastic effect of these compounds on primary cells derived from two MPNSTs of Neurofibromatosis type 1 patients. RESULTS: Exisulind and Sulindac Sulfide showed a dramatic time- and dose-dependent growth inhibitory effect with IC50-values of 120 μM and 63 μM, respectively. The decrease in viability of the tested cells correlated with induction of apoptosis. Treatment with 500 μM Exisulind and 125 μM Sulindac Sulfide for a period of 2 days increased the rate of apoptosis 21-27-fold compared to untreated cells. Reduced expression of RAS-GTP and phosphorylated ERK1/2 was detected in treated MPNST cells. Moreover, elevated levels of phosphorylated SAPK/JNK were found after drug treatment, and low activation of cleaved caspase-3 was seen. CONCLUSIONS: Our results suggest that this class of compounds may be of therapeutic benefit for Neurofibromatosis type 1 patients with MPNST.